Are kinetic chain rowing exercises relevant in shoulder and trunk injury prevention training?. Issue 4 (27th March 2011) - De Mey, K; Danneels, L; Cagnie, B; Cools, A
Abstract : Background: Recent guidelines emphasise the importance of functional kinetic chain exercises during injury prevention training. Knowledge of muscle activation levels during various unilateral rowing exercises is lacking. Objective: To describe and compare the activation levels of scapulothoracic and lumbopelvic muscle parts during eight variations of the high rowing exercise. Design: Descriptive study. Exercise performance was standardised and individualised based on height, age and body weight. Setting: Controlled laboratory study at Ghent University (Belgium). Participants: 30 young healthy volunteers with a history of being active in sports and able to perform the exercises correctly. Interventions: Activation levels of the upper trapezius (UT) and lower trapezius (LT) muscles of the dominant shoulder, and multifidus (MF) and erector spinae (ES) muscles at both sides of the trunk were investigated. Exercises were performed in front of a pulley apparatus. Main outcome measurements: Individual muscle activation levels captured by surface Electromyography. Results: Shoulder muscle activation was characterised by superior LT (>12.5% MVIC) over UT (<7.12% MVIC) muscle activation across exercises. Rowing in a static unipedal squat position revealed highest LT muscle activation (18.33% MVIC). Upright exercises (squatted or lunged) showed generally higher trunk muscle activation levels compared to a sitting or standing execution. Superior MF (>21% MVIC) over ES (<30.13% MVIC) muscle activation was found during all upright exercises, except during static bipedal squatting. Highest MF muscle activation was found heterolateral to arm movement during the dynamic single leg squat version of the exercise (33.26% MVIC; p<0.05). Conclusion: High rowing exercises recruit posterior shoulder and trunk muscles relevant in injury prevention training. Unilateral rowing during a single leg squat position or movement seems most favourable for athletic injury prevention training purposes.